Anatomical variants of the vertebral artery: insights from cadaveric and radiological studies-a review - Basagoudanavar, Shrikrishna H.; Gadwal, Deepa (International Journal of Advances in Medicine, 2025)
Vertebral artery (VA) anatomical variations pose significant clinical challenges in neurosurgical, diagnostic, and endovascular interventions. This review aims to consolidate cadaveric and radiological evidence to map the morphologic spectrum and prevalence of such variants. A comprehensive search strategy was applied to PubMed using Boolean terms, retrieving 446 articles. Following strict inclusion criteria, 31 studies were selected. The most common variant identified was the origin of the left VA from the aortic arch, observed in 13 studies with a frequency range of 0.79%–9.3%. Entry level variations at cervical vertebrae C3–C7, hypoplasia (16.1%–59.3%), duplication (~0.16%), fenestration (~0.4%), and other anomalies such as triplication and abnormal origins from the brachiocephalic or common carotid artery were also reported. Course-related anomalies including tortuosity and anomalous trajectories further highlight the importance of preoperative imaging. Radiological studies offered population-level data, while cadaveric studies revealed detailed morphological nuances. Geographic variation in findings underscores the role of ethnicity and embryological development. The findings emphasize the need for standardized nomenclature, enhanced imaging protocols, and greater awareness among clinicians to mitigate intraoperative risks and improve patient outcomes.